Los Angeles in the 1930s the WPA guide to the City of Angels (Univ. of California Press, 2011)
Describes a pivotal moment in Los Angeles history, when writers like Raymond Chandler, Nathanael West, and F. Scott Fitzgerald were creating the images and associations--and the mystique--for which the City of Angels is still known. Los Angeles in the 1930s a guide to the contemporary culture, with a brief L.A. history, revisiting the Spanish colonial period, the Mexican period, the brief California Republic, and finally American sovereignty